Rapidly fabricated triboelectric nanogenerator employing insoluble and infusible biomass materials by fused deposition modeling. (February 2020) - Yu, Zhaohan; Wang, Yunming; Zheng, Jiaqi; Xiang, Yi; Zhao, Peng; Cui, Jingqiang; Zhou, Huamin; Li, Dequn
Abstract: Limited in their insolubility and non-melting properties, biomass materials are hard to be directly applied to the fabrication of triboelectric nanogenerator (TENG), especially lignin, chitosan (CTS) and cellulose. To tackle these challenges, a novel strategy is proposed for the rapid preparation of insoluble and infusible biomass material based triboelectric nanogenerator (IBTENG) using digital fabrication methods. Insoluble and infusible biomass materials and polydimethylsiloxane (PDMS) were carried by polyamide (PA) and polyethylene (PE) tubes, respectively, to fabricate the porous positive and negative electrodes using fused deposition modeling (FDM). The optimal output of the IBTENG reaches 308 V and 61.6 μA at the frequency of 30 Hz and the power of 3.5 W, while the energy conversion efficiency reaches 78% and the power density is 5.93 W/m 2 . Compared with TENG prepared by traditional materials, IBTENG with outstanding performance is an extremely competitive candidate for eco-friendly energy-conversion devices based on ubiquitous mechanical energy. Further, it can be utilized directly to light two series-connected LED bulbs rated at 85 V and 3 W. This detailed investigation presented herein is a simple and universal approach for the direct use of insoluble and infusible biomass powders in the field of high-performance triboelectric devices, eliminating the need for complicated dissolution and after processing, which enables rapid fabrication of individualized and materially diverse devices. Graphical abstract: A novel strategy is proposed for the rapid fabrication of insoluble and infusible biomass material based triboelectric nanogenerators (IBTENG) with microstructure using digital preparation methods. The rapidly fabricated and eco-friendly IBTENG exhibits satisfactory performance (U = 308 V, I = 61.6 μA, ŋ  = 78%, Q = 5.93 W/m 2 ) and can directly illuminate two series-connected LED bulbs rated at 85 V and 3 W. Image 1 Highlights: Insoluble and infusible biomass materials can be directly applied to rapidly prepare IBTENG with microstructure using FDM. Microstructure was formed inside the friction layer, which effectively improved the triboelectric properties of IBTENG. The rapidly fabricated and eco-friendly IBTENG exhibits satisfactory performance (U = 308 V, I = 61.6 μA, Q = 5.93 W/m 2 ). This IBTENG can directly illuminate two series-connected bulbs rated at 85 V and 3 W.